Relationships between digestive, circulatory and urinary systems in portuguese primary textbooks - Carvalho, Graça Simões de (2007)
We found earlier that Portuguese primary school pupils and teachers (in contrast to French ones) show difficulties in three main concepts of digestion processes: sequence of the digestive track representation; absence of blood absorption and lack of relationship between digestive, circulatory and urinary systems. In this study we analysed 63 Portuguese primary schoolbooks (1920-2005), focused on: - Text information – reference to blood absorption and association of the digestive system to other human systems; - Images information – presence or absence of image “confusion” (when the sequence of the digestive tract is not presented in a clear way), blood absorption representation and association of the digestive system to other human systems. Results showed that, in general, the text of primary school textbooks (i) refers the nutrients absorption into the blood, (ii) but mentions scarcely the association of the digestive function with the other human functions. The images of the digestive apparatus (i) always present “confusion”, (ii) rarely refer to absorption of nutrients into the blood, and (iii) never associate the digestive apparatus with other human systems. A brief comparison with French textbooks showed that they present more straight representations of the digestive tract sequence (no “confusion”) and generally do not relate it to blood circulation. Since other studies have also showed that French pupils and teachers usually do not draw this “confusion” and do not associate the digestion process to blood absorption, our results suggest that inadequate images of textbooks may be didactical obstacles to accurate learning.